Magnetic chains of Fe3 clusters in the Fe3YO2 butterfly molecular compound. Issue 9 (20th February 2020) - Rubín, Javier; Badía-Romano, Laura; Luis, Fernando; Mereacre, Valeriu; Prodius, Denis; Arauzo, Ana; Bartolomé, Fernando; Bartolomé, Juan
Abstract : Supramolecular magnetic chains of Fe3 cluster in a molecular complex. Abstract : The "butterfly" molecule [Fe3 Y(μ3-O)2 (CCl3 COO)8 (H2 O)(THF)3 ] (in brief Fe3 YO2 ) includes three Fe 3+ ions which build a robust Fe3 cluster with a strong intracluster antiferromagnetic exchange and a total spin S = 5/2. It represents the starting magnetic system to study further interactions with magnetic rare earths when Y is replaced with lanthanides. We present heat capacity and equilibrium susceptibility measurements below 2 K, which show that each cluster has a sizeable magnetic anisotropy pointing to the existence of intercluster interactions. However, no phase transition to a long-range magnetically ordered phase is observed down to 20 mK. The intercluster interaction is analysed in the framework of the one-dimensional Blume–Capel model with an antiferromagnetic chain interaction constant J / k B = −40(2) mK between Fe3 cluster spins, and a uniaxial anisotropy with parameter D / k B = −0.56(3) K. This is associated to single chains of Fe3 clusters oriented along the shortest intercluster distances displayed by the crystal structure of Fe3 YO2 . Ac susceptibility measurements reveal that the magnetic relaxation is dominated by a quantum tunnelling process below 0.2 K, and by thermally activated processes above this temperature. The experimental activation energy of this single chain magnet, E a / k B = 3.4(6) K, can be accounted for by the combination of contributions arising from single-molecule magnetic anisotropy and spin–spin correlations along the chains.